Prevalence of excessive negative energy balance in commercial United Kingdom dairy herds. (June 2019) - Macrae, A.I.; Burrough, E.; Forrest, J.; Corbishley, A.; Russell, G.; Shaw, D.J.
Highlights: Excessive negative energy balance affected 52% of UK dairy cows in late pregnancy. In the first 20 days after calving, 75.2% of UK dairy cows were affected. The herd prevalence of excessive negative energy balance was 37.5% in late pregnancy and 59.8% in early lactation. Such excessive negative energy balance has been associated with harmful effects on cow health, milk production and fertility. Abstract: The objectives of this study were to determine the individual animal and herd level prevalence of excessive negative energy balance (eNEB) in commercial UK dairy herds. Between April 2006 and March 2015, blood samples from 84, 369 individual cows from 1748 different UK farms were received by a commercial laboratory service specializing in dairy cow nutritional monitoring. Following removal of all potential duplicate cows, the final dataset comprised 69, 161 unique individual cows. The prevalence of eNEB was determined using plasma thresholds of β-hydroxybutyrate (BHB), non-esterified fatty acids (NEFA) and glucose. Overall prevalence of subclinical ketosis (SCK) in the first 20 days of lactation was 28.5%, 17.3% and 11.7% using BHB thresholds of 1.0, 1.2 and 1.4 mmol/L respectively. Prevalence of NEFA values ≥0.5 mmol/L in the last 10 days prior to calving was 26.0%, and 40.3% of cows had NEFA values ≥0.7 mmol/L in the first 20 days in milk (DIM). Combining BHB, NEFA and glucose showed that 52.0% of cows had one or more of the three biochemical measures of energy balance outside the respective threshold value in the last 10 days pre-calving, and 75.2% of cows showed a similar biochemical pattern in the first 20 DIM. The median herd prevalence of elevated BHB and/or NEFA was 37.5% in late pregnancy and 59.8% in the first 20 DIM, with substantial herd variation. Using multiple measures for the assessment of energy balance, this study has shown that eNEB affects substantial numbers of UK dairy cows.